Exposure to per- and poly-fluoroalkyl substances in association to later occurrence of type 2 diabetes and metabolic pathway dysregulation in a multiethnic US populationResearch in context - Vishal Midya; Meizhen Yao; Elena Colicino; Dinesh Barupal; Xiangping Lin; Chris Gennings; Leda Chatzi; Veronica Wendy Setiawan; Ruth J.F. Loos; Ryan W. Walker; Douglas I. Walker; Damaskini Valvi (EBioMedicine)
Summary: Background: Growing evidence suggests that exposure to per- and polyfluoroalkyl substances (PFAS) are linked to an increased risk of type 2 diabetes (T2D); however, the effect of PFAS mixtures and underlying mechanisms are not well understood. We examined the associations between exposure to PFAS mixture with later T2D diagnosis and underlying metabolic dysregulations. Methods: We conducted a nested case–control study within BioMe, an electronic health record-linked biobank of >65,000 patients seeking primary care at Mount Sinai Hospital, New York, since 2007. After excluding prevalent T2D cases at baseline, we selected 180 incident T2D cases (33% African Americans, 33% Hispanics, 33% Whites) and 180 age, sex, and ancestry-matched T2D-free controls. In prediagnostic plasma collected at baseline (∼6 years before diagnosis), we quantified seven PFAS and untargeted metabolomic profiles. We used Weighted Quantile Sum regression to evaluate the PFAS mixture association with the odds for incident T2D. We analysed the associations between ∼650 annotated metabolites and the PFAS mixture or T2D odds using Hierarchical Bayesian Weighted Quantile Sum and logistic regression, respectively, adjusting for matching factors and other confounders. Pathway enrichment analyses were performed using Mummichog. Findings: Each tertile increase in the PFAS mixture was associated with higher odds of incident T2D (OR [95% CI] = 1.31 [1.01, 1.70]), with Perfluorooctane Sulfonate (PFOS) having the highest contribution to this association. Metabolites associated with both the PFAS mixture and T2D odds were 5-hydroxytryptophan, glucoheptulose, and sulfolithocholylglycine; the associations with sulfolithocholylglycine survived multiple testing corrections. Pathways associated with both the PFAS mixture and T2D were glutamate metabolism, arginine and proline metabolism, and drug metabolism—cytochrome p450. Interpretation: Exposure to PFAS mixtures may be associated with increased odds for T2D in multiethnic populations via dysregulations in amino acid and drug metabolism. Larger investigations in multiethnic populations are required to elucidate the potential PFAS contribution to metabolic alterations and T2D risk. Funding: National Institutes of Health (R01ES033688, P30ES023515, R21ES035148, R35ES030435, R01ES032242, R01ES034521, R01ES029944, R01ES030364, U01HG013288, R21ES037112 and P30ES007048).